2003
DOI: 10.1021/ef020272i
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Pathways for Monoethanolamine in a CO2 Capture Facility

Abstract: One of the highest priorities in carbon sequestration science is the development of techniques for CO 2 separation and capture, because it is expected to account for the majority of the total cost (∼75%). The most common currently used method of CO 2 separation is reversible chemical absorption using monoethanolamine (MEA) solvent. In the current study, solvent degradation from this technique was studied using degraded MEA samples from the IMC Chemicals Facility in Trona, California. A major pathway to solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
297
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(307 citation statements)
references
References 13 publications
8
297
1
1
Order By: Relevance
“…Most of the amines tested showed very little oxidative degradation and this makes it difficult to propose degradation mechanisms for the formation of new degradation compounds. In general it seems like the formation of degradation compounds follows the same patterns as earlier described for the formation of de-methylated amines (secondary and tertiary amines) or secondary products as HEF analogues, HEI, OZD analogues, alkylamines and ammonia (da Silva et al, 2012; Lepaumier et al, 2011b;Lepaumier et al, 2009b;Strazisar et al, 2003;.…”
Section: Other Aminessupporting
confidence: 62%
See 1 more Smart Citation
“…Most of the amines tested showed very little oxidative degradation and this makes it difficult to propose degradation mechanisms for the formation of new degradation compounds. In general it seems like the formation of degradation compounds follows the same patterns as earlier described for the formation of de-methylated amines (secondary and tertiary amines) or secondary products as HEF analogues, HEI, OZD analogues, alkylamines and ammonia (da Silva et al, 2012; Lepaumier et al, 2011b;Lepaumier et al, 2009b;Strazisar et al, 2003;.…”
Section: Other Aminessupporting
confidence: 62%
“…Thermal degradation with CO2 was studied by Davies, Lepaumier and Eide-Haugmo (Davis, 2009;Eide-Haugmo, 2011;Lepaumier et al, 2009a) and oxidative degradation by Lepaumier (Lepaumier et al, 2009b). Increased attention on oxidative degradation was seen after pilot plant samples showed high degree of similarity to degradation compounds found in oxidative degradation experiments (da Silva et al, 2012;Lepaumier et al, 2011a;Strazisar et al, 2003). The oxidative degradation experiments reported have been performed in variations of two setups, either in a closed-batch reactor at elevated temperature and oxygen pressure (Lepaumier et al, 2009b;Supap et al, 2001;Wang and Jens, 2011) or in an open-batch reactor at 55 °C, where the solution would be sparged with a wet gas blend of CO2 and O2/air (da Silva et al, 2012;Goff and Rochelle, 2004;Lepaumier et al, 2011b;Sexton and Rochelle, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal degradation has been studied by several research groups over a long period of time (Davis and Rochelle, 2009;Eide-Haugmo, 2011;Lepaumier et al, 2009a;Polderman et al, 1955) while oxidative degradation has received increased attention the last decade (Goff and Rochelle, 2004;Lepaumier et al, 2009;Rooney et al, 1998;Supap et al, 2001) as it was discovered that oxidative degradation compounds are the main products under real plant conditions (da Silva et al, 2012;Lepaumier et al, 2011a;Strazisar et al, 2003). Increased insight into the degradation mechanisms, through knowledge of stoichiometry, kinetics, and chemical pathways, may result in methods for eliminating or strongly reducing degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The initial mechanisms are still unclear, but the general impression is that the mechanisms either start with abstraction of an electron from the lone pair of nitrogen or abstraction of hydrogen from the nitrogen, α-carbon, or β-carbon, or a combination of these depending on the amine structure, nature of oxidants, pH, solvent effects and concentrations (Bedell, 2009;Chi and Rochelle, 2002;Rochelle, 2004, 2006;Hull et al, 1967;Hull et al, 1969;Rosenblatt et al, 1967;Sexton, 2008) Secondary degradation compounds are formed by reactions between primary degradation compounds and amines forming for example amides as N-(2-hydroxyethyl)-formamide (HEF), N-(2-hydroxyethyl)-acetamide (HEA) and N,-oxamide (BHEOX) from MEA and acid, or aldehyde and oxygen, and imidazoles as N-(2-hydroxyethyl)imidazole (HEI) from ammonia, MEA and several aldehydes. Lately several mechanisms have been suggested for the formation of secondary degradation compounds (da Silva et al, 2012;Lepaumier et al, 2011a;Strazisar et al, 2003). However, there are still many unanswered questions regarding factors influencing the formation of these degradation compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The MEA reclaimer waste is considered to be a hazardous waste (24). This was further proved by a study performed by NETL, Pittsburgh, which identified chemical species (MEA, ammonia, 3-hydroxyethylamino-N-hydroxyethyl propanamide, 4-hydroxyethyl-2-piperizinone, 2-hydroxyethylamino-N-hydroxyethyl acetamide, and N-acetyletylethanolamine) in the reclaimer waste that are considered to be hazardous (25,26). Entrainment of MEA with the treated flue gas will be at most a few parts per million and is minimized with the addition of a wash section in the top portion of the absorber column.…”
Section: Environmental Impactsmentioning
confidence: 95%